Achieving security for images by LSB and MD5 - Alahmad, Mohammad; Alshaikhli, Imad Fakhri Taha; O. Alhussainan, Sondos (Design for Scientific Renaissance, 2012)
Steganography is a technique used to hide a message inside video, audio, or image files. A hash function is a transformation that takes input values and returns a fixed-size string, which is called the hash value. In this paper, a message will be hidden inside an image by using the Least Significant Bits (LSB replacement) technique. This method creates a random dispersion of bits of the message in the picture, and it would be difficult to extract the message without the password key .After creation of the hidden message, the image will pass it in hash function to obtain hashing value using the MD5 technique. This value will be fixed as long as there has been no change to the picture. If it has been manipulated after hiding the information, it can be discovered by the owner of the key because the serial hash value will be changed.